(untitled) (Research, Society and Development, 2021)
Studies involving the use of iron ore tailings from the beneficiation process in different market niches are increasingly necessary due to the large environmental damage caused by their disposal in dams, since they are waste generated in high volumes and which have low economic value for mining companies The main purpose of this study was to investigate mechanical properties of hot mix asphalt mixture containing iron ore flotation tailing. For this, a mixture containing iron ore flotation tailing and a control mixture with natural aggregates and stone dust were prepared according to the Marshall methodology and tests of stability and flow, indirect tensile strength, resilient modulus, fatigue test and dynamic creep tests were conducted. Results show that the mixture with iron ore flotation tailing had performed technically appropriate, due to the similarity of mechanical properties of the control mixture. Therefore, the results obtained revealed that the iron ore flotation tailing presented technical characteristics appropriate to its use incorporated into hot mix asphalt. In addition, their use as an alternative material in asphalt pavements can generate environmental benefits by reducing the volume of material deposition in tailings landfills and exploration areas for mineral aggregate mining.